2020
DOI: 10.1007/s00508-020-01764-0
|View full text |Cite
|
Sign up to set email alerts
|

Structured ICU resource management in a pandemic is associated with favorable outcome in critically ill COVID‑19 patients

Abstract: Summary Introduction On February 25, 2020, the first 2 patients were tested positive for severe acute respiratory syndrome coronavirus‑2 (SARS-CoV-2) in Tyrol, Austria. Rapid measures were taken to ensure adequate intensive care unit (ICU) preparedness for a surge of critically ill coronavirus disease-2019 (COVID-19) patients. Methods This cohort study included all COVID-19 patients admitted to an ICU with confirmed or strongly suspected COVID-19 in the State of Tyrol, Austria. Patients were recorded in the T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 26 publications
0
31
0
3
Order By: Relevance
“…A total of 135/145 patients agreed to participate in the neurological follow‐up 3 months after disease onset and were evaluated using a structured neurological assessment between April 2020 and September 2020. Patients who died during the acute phase were not included in this study, and the ICU mortality rate was 19% as reported elsewhere [18]. Importantly, the Tyrolean healthcare system was never overloaded, and all patients received full medical support [18].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 135/145 patients agreed to participate in the neurological follow‐up 3 months after disease onset and were evaluated using a structured neurological assessment between April 2020 and September 2020. Patients who died during the acute phase were not included in this study, and the ICU mortality rate was 19% as reported elsewhere [18]. Importantly, the Tyrolean healthcare system was never overloaded, and all patients received full medical support [18].…”
Section: Methodsmentioning
confidence: 99%
“…Patients who died during the acute phase were not included in this study, and the ICU mortality rate was 19% as reported elsewhere [18]. Importantly, the Tyrolean healthcare system was never overloaded, and all patients received full medical support [18].…”
Section: Methodsmentioning
confidence: 99%
“…Due to numerous influencing factors different cohorts from various areas have demonstrated widely varying mortality rates and characteristics of intensive care unit (ICU) patients. A meta-analysis published in June 2020 found ICU mortality rates ranging from 14–84% [ 3 ], which has shown the importance of observing regional conditions separately in order to have a better understanding of major factors influencing outcome [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…In Tyrol, Austria, comprising 750,000 inhabitants we established the Tyrolean COVID-19 intensive care registry (Tyrol-CoV-ICU-Reg) at the beginning of the first surge of the pandemic in March 2020. Characteristics and outcomes of the first period have previously been published [ 4 ]. Since then, we continued the registry throughout the second period of the COVID-19 crisis.…”
Section: Introductionmentioning
confidence: 99%
“…As of December 21, around 75 million infections have been documented around the globe with an overall mortality rate of 2.23% [ 1 ]. Although most patients with SARS-CoV-2 infections have been reported to develop mild to moderate symptoms, patients with severe respiratory insufficiency requiring admission to the intensive care unit (ICU) are at a high risk of major morbidity and subsequently have high mortality rates [ [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] ]. Several cohort studies have reported the characteristics of and outcomes from COVID-19 pneumonia in these critically ill patients [ 2 , 4 , 5 , 11 , 12 , 20 , 23 ].…”
Section: Introductionmentioning
confidence: 99%